2019
DOI: 10.1155/2019/4108474
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Plasma Cell-Free DNA Methylation Profiling Identifies Potential Biomarkers for Lung Cancer

Abstract: As a noninvasive blood testing, the detection of cell-free DNA (cfDNA) methylation in plasma has raised an increasing interest due to diagnostic applications. Although extensively used in cfDNA methylation analysis, bisulfite sequencing is less cost-effective. In this study, we investigated the cfDNA methylation patterns in lung cancer patients by MeDIP-seq. Compared with the healthy individuals, 330 differentially methylated regions (DMRs) at gene promoters were identified in lung cancer patients with 33 hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…For SLC9A3R2 gene, previous studies have proven that this gene is involved in the colon cancer [35] and breast cancer [36] . In addition, the aberrant methylation status of SLC9A3R2 in cell free-DNA could be a potential biomarker for lung cancer [37] . However, the study of both SLC9A3R2 and ZC3H3 in liver cancer is lacked.…”
Section: Discussionmentioning
confidence: 99%
“…For SLC9A3R2 gene, previous studies have proven that this gene is involved in the colon cancer [35] and breast cancer [36] . In addition, the aberrant methylation status of SLC9A3R2 in cell free-DNA could be a potential biomarker for lung cancer [37] . However, the study of both SLC9A3R2 and ZC3H3 in liver cancer is lacked.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using genome-wide methylation profiling of serum/plasma cell-free DNA have identified potential biomarkers for clinical utility. For instance, Xu et al using MeDIP-seq approach reported 10 significant differentially methylated genes as potent biomarker for lung cancer clinical application (Xu et al, 2019). Similarly, using genome-wide methylome profiling and Sequenom MassARRAY approach, it was reported that promoter methylation of CASZ1, CDH13, and ING2 could serve as a potent noninvasive biomarker for detection of esophageal cancer at early stage (Wang H.Q.…”
Section: Clinical Application Of Epigenetic Biomarker In Liquid Biopsmentioning
confidence: 99%
“…The B3GAT2 gene is a trans-membrane protein involved in the synthesis of a carbohydrate epitope, a sulfated trisaccharide involved in cellular migration. 32 Although gene sequencing data showed higher expression of the transcript than control, there is scant evidence of B3GAT2's involvement in oocyte maturation. Hence further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, downregulation of inhibin beta B unit might be due to the action of FSH hormone in in vitro matured COCs. 32 Matured COCs do not require FSH action, providing negative signals to stop the secretion of FSH. 43 CPSF1 is involved in the cleavage of the 3' signaling region from a newly synthesized pre-messenger RNA (pre-mRNA) molecule in the process of gene transcription.…”
Section: Discussionmentioning
confidence: 99%